Trends and challenges of reforming housing and utilities management in Russia - Vasily V. Butyrin, Violetta V. Rokotyanskaya,; Mutsalov, Shadid Sh.; Usanov, Aleksandr Yu.; Fefelova, Natalia P. (Opción, 2019)
The article considers the concept of housing and utilities services and describes its main features in Russia via comparative qualitative research methods. As a result, in order to significantly improve the quality of service for residential buildings in Russia, it is necessary to refer to the experience of Western countries. In conclusion, when borrowing any foreign experience, it is necessary to take into account all the local conditions, various aspects and the situation within the country, and in order to work effectively, the foreign experience must be properly worked out and only then be put into practice.